2016
DOI: 10.4193/rhin15.272
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of medical, psychological and socio-economic factors influencing the severity of chronic rhinosinusitis

Abstract: Background: Chronic rhinosinusitis (CRS) is a common and debilitating disorder. Little is known about the epidemiology of this disease. The aims of the study were to identify differences in socio-economic variables and quality of life between patients with chronic rhinosinusitis and healthy controls, to identify any significant associations between CRS and other medical co-morbidities, psychiatric disease or environmental exposure and to explore the experience of CRS from the perspective of CRS sufferers.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 18 publications
6
44
2
Order By: Relevance
“…These study data are useful in two ways: firstly, it provides a reference generic QOL measurement in UK patients with CRS for future researchers. We have shown the mean SNOT‐22 scores to be in line with a large UK epidemiological study, and hence, the data provided here can be used as a benchmark for future patient cohorts. Additionally, they allow comparison of CRSsNPs with other chronic disease states, the health index scores obtained from the EQ‐5D data indicate it has a significant impact on patients.…”
Section: Discussionsupporting
confidence: 76%
“…These study data are useful in two ways: firstly, it provides a reference generic QOL measurement in UK patients with CRS for future researchers. We have shown the mean SNOT‐22 scores to be in line with a large UK epidemiological study, and hence, the data provided here can be used as a benchmark for future patient cohorts. Additionally, they allow comparison of CRSsNPs with other chronic disease states, the health index scores obtained from the EQ‐5D data indicate it has a significant impact on patients.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, there was a significant association between smoking and CRS. This is in accordance with the results from some studies, although no such association was found in a recent case‐control study with objectively verified CRS . There are still few studies on the effect of environmental factors on CRS, but there are some results indicating that air pollution, the use of woodstoves as principal source of heat and exposure to gas, fumes and dust at work may be related to an increased risk of CRS .…”
Section: Discussionsupporting
confidence: 89%
“…However, a study by Philpott and colleagues of CRS patients from specialty clinics found no association between CRS and social class, index of multiple deprivation, and education. [29] Surrogate measures of SES (i.e. Medical Assistance and income) are not always interchangeable, possibly accounting for conflicting findings.…”
Section: Discussionmentioning
confidence: 99%